P345 Correlates of consistent condom use among urban adolescents attending high-school in panama. (14th July 2019) - Gabster, Amanda; Ranaweera, Indira; Sunku, Nisha; Menezes, Lynette; Martinez, Alexander; Dyamond, José; Aizprua, Betsy; Castillero, Omar; Castillo, Jorge; Pascale, Juan
Abstract : Background: Consistent condom use, defined as using a condom in every sexual encounter, is an effective measure for preventing sexually transmitted infections (STIs). However, few studies have examined condom use among Latin American youth. This study estimated the correlates of reported condom use among school-going adolescents in four urban sites of Panama during 2015–2018, where one site was studied each year. Additionally, we assessed condom use practices among adolescents with herpes simplex virus 2 (HSV2). Methods: Adolescents aged 14 -19 years completed a self-administered tablet-based questionnaire that measured reported sexual history and practices. Blood samples from sexually experienced adolescents were evaluated for HSV2. Associations between sociodemographic characteristics, sexual behaviors, HSV status and condom use were estimated with the chi-square statistic. Univariate odds ratios (ORs) and age-adjusted (AOR) analyses were performed. Results: Among 2466 adolescents, there was no significant difference in reported sexual activity prevalence among males (58.4%) and females (56.7%) (p=0.402). Reported consistent condom use was low (25%) among sexually active participants. Older adolescents (17–19 years) were less likely to report consistent condom use (17 years OR=0.63, 95% CI 0.41–0.97 and 18–19 years OR=0.66, 95% CI 0.43–0.99). Males had higher reports of consistent condom use (AOR=1.65, 95% CI 1.08–2.53) compared to female adolescents. Adolescents reporting two or more lifetime sexual partners (OR=0.43, 95% CI 0.31–0.61), current sexual activity (OR=0.70, 95% CI 0.51–0.96), and sex with a casual partner (OR=0.60, 95% CI 0.44–0.82), were less likely to report consistent condom use. HSV2 prevalence was 20.8% among sexually active participants. HSV2 seropositivity was not correlated with reported condom use (p=0.124). Conclusion: Reported consistent condom use among sexually active, school-going adolescents in Panama was low, particularly among females and older adolescents. Condom use interventions should include information regarding effective condom negotiation strategies between sexual partners. These strategies are important throughout adolescence. Disclosure: No significant relationships.